Differential Diagnosis of Chest Pain Syndrome: Thoracalgia and Cardialgia - Kudrin, A.P.; Borzykh, N.O.; RoiІ.V.; Mosiichuk , S.M. (TERRA ORTHOPAEDICA, 2024)
Summary. The objective of the study was to conduct a differential diagnosis of chest pain and to identify the percentage of patients with a cardiac component. Material and Methods. 147 patients were examined; mean age was 43.2±1.9 years. Patients’ complaints and risk factors were carefully analyzed. MRI examination, radiography of the thoracic spine, electrocardiography, echocardiography, and bicycle ergometry were performed. Exclusion criteria were as follows: acute isolated pathology of the cardiovascular system (myocardial infarction, angina pectoris), deforming and traumatic changes in the spine (grade 3-4 scoliosis, compression fractures of the vertebral bodies, chest deformities). Results. The patients were divided into 3 groups: patients with spinal degenerative disc disease, patients with cardiac symptoms and spinal variables, and a group that mainly suffered from cardiovascular disease. Electrocardiography, echocardiography, and bicycle ergometry were performed to objectively confirm the obtained data. Electrocardiography changes were observed in 29.2% of patients. Among patients with degenerative disc disease, electrocardiography changes occurred in 4%, while they were noted in 21.4% of cases in the group with mixed pathology and 100% in the group of patients with signs of cardiovascular disease. According to echocardiography, 28.6% had cardiac changes. The most common cause was atherosclerosis (50%) and hypertension (21.4%). By observation groups, the level of changes and their severity significantly increased from group 1 to group 3. Bicycle ergometry gave a “positive” test in 20% of cases. Diagnostic procedures revealed a tendency to establish the causes of pain. MRI and electrocardiography play the most important role. The data obtained allow us to conclude that the cause of pain syndrome in group 3 of patients is based on heart and vascular disease. This group is transferred to the supervision of a cardiologist, so in the further study, we paid attention to the groups with spinal osteochondrosis (75) and the mixed group (42). The degree of severity of changes, both quantitatively and in terms of the severity of concomitant pathology, is noteworthy. Thus, in patients with spinal degenerative disc disease, the level of comorbidities reached 18.7%; in patients with cardiac symptoms and changes in the spine, it was 50%, which significantly aggravates their course. The high level of anxiety in the group as a whole is noteworthy, which creates a negative background for treatment and requires mandatory correction. A program of appropriate treatment in the group with combined pathology should be created taking into account its cardiological component. Conclusions. A careful analysis of the results indicates the presence of a group of patients with concomitant cardiac pathology that requires additional correction in the complex of generally accepted therapeutic measures.